2022
DOI: 10.1098/rspb.2022.0622
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle function underpins muscle spindle abundance

Abstract: Muscle spindle abundance is highly variable within and across species, but we currently lack any clear picture of the mechanistic causes or consequences of this variation. Previous use of spindle abundance as a correlate for muscle function implies a mechanical underpinning to this variation, but these ideas have not been tested. Herein, we use integrated medical imaging and subject-specific musculoskeletal models to investigate the relationship between spindle abundance, muscle architecture and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 49 publications
(129 reference statements)
1
24
0
Order By: Relevance
“…Instead, any inference of spindle provision should be based on a suitably transformed linear relationship 12 . Subsequently, the residual value of the linear regression of the log-transformed spindle number and muscle mass as an unbiased measure has become the prevailing descriptor of spindle abundance 10 , 11 , 13 . Residual values are homogenously distributed, allow for back-transformation calculations of spindle number, and provide the most unbiased comparative measure of relative spindle abundance 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, any inference of spindle provision should be based on a suitably transformed linear relationship 12 . Subsequently, the residual value of the linear regression of the log-transformed spindle number and muscle mass as an unbiased measure has become the prevailing descriptor of spindle abundance 10 , 11 , 13 . Residual values are homogenously distributed, allow for back-transformation calculations of spindle number, and provide the most unbiased comparative measure of relative spindle abundance 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The model analysis included a total of 23 individual muscles, spanning a range of estimated muscle spindle abundance. The authors found that the absolute number of muscle spindles was related to muscle fibre length, and predictive of total muscle length, its velocity profile, and to a certain extent to the force-generating capacity of muscles during walking [2]. Their findings suggest an intriguing correlation between muscle mechanical roles and spindle abundance.…”
mentioning
confidence: 99%
“…The findings from Kissane et al . [2] suggest an important hypothesis about the relationship between a muscle's mechanics and spindle sensory organ abundance and highlight the importance of considering the relationships between muscle sensing and mechanics.…”
mentioning
confidence: 99%
See 2 more Smart Citations